Financial Gerontology - Erik Selecky; Andrzej Klimczuk (Encyclopedia of Gerontology and Population Aging, 2020)
Financial gerontology can be defined as investigating relations between finances and aging. Authors such as Neal E. Cutler, Kouhei Komamura, Davis W. Gregg, Shinya Kajitani, Kei Sakata, and Colin McKenzie (Kajitani et al. 2017) affirm that financial literacy is an effect of aging with concern about the issue of finances, as well as stating that it is the effect of longevity and aging on economies or the financial resilience of older people.
Keywords: J14; G29; 330; Financial Gerontology